Colonial Famine Relief and Development Policies: Towards an Environmental History of Northern Ghana. (1st January 2011) - Grischow, Jeff; Weiss, Holger
Since the 1980s, scientific experts have made a number of recommendations for averting food insecurity and famine in Northern Ghana and other dryland areas of West Africa. These studies are based on regional meteorological data, and their suggestions include early warning systems, smallholder agricultural development, and the depopulation of densely settled regions. Much of this literature posits two main hypotheses: that regional data can provide a reliable indicator of the potential for harvest failure, and that the recommended policy actions can work because they are new and innovative, without historical precedent. This article delves into the colonial past to challenge both of these hypotheses. Using Northern Ghana as a case study, we question the usefulness of regional data for understanding food insecurity, and we show that the supposedly novel ideas of the present in fact have a strong colonial lineage.